Bioaccumulation of heavy metals in Acanthopagrus latus collected from Iraqi marine waters - Al-Najare, G.A.; Hantoush, A.A.; Al-Shammary, A.C.; Al- Saad, H.T. (Iraqi Journal of Aquaculture, 2022)
Concentrations of cadmium, cobalt, cupper, iron, manganese and nickel were determined in four organs (liver, gills, ovaries and muscles) of Acanthopagrus latus, which collected from Iraqi marine waters during the period between November 2010 and October 2011. Heavy metals have been determined by means of Atomic Absorption Spectrophotometry. The fish average weight was 61.2 g and the average length was 144 mm. Nickel showed the highest values in liver, gills and muscles during spring (201.19, 190.00 and 148.00 μg/gm dry weight), respectively. While cobalt showed the lower value (1.12 μg/gm dry weights) in the liver and cadmium showed its lower value (1.23 μg/gm dry weights) in the gills during winter. Muscles showed constant levels of heavy metals, it showed the lower values (not detected) during winter. Ovaries showed high levels for all heavy metals during spring, but its value still instable during the other seasons. This study showed that the concentration of heavy metals distributed in the organs was as follows: liver > gills > muscles > ovaries, while the heavy metals concentration had been distributed during the seasons as follow: winter > spring > autumn > summer.